Earthworms (Oligochaeta: Lumbricidae) of Georgia, Caucasus: distribution and biodiversity - Kokhia, Mzia; Gorgadze, Oleg; Tsiklauri, Khatuna; Lortkipanidze, Manana; Nebieridze, David; Kuchava, Madona (Zootaxa, 2024)
The article attempts to present the species composition and distribution of earthworms in Georgia—one of the central countries of the Caucasus. According to long-term research, about 90 species of earthworms belong to 13 genera. They have been identified throughout Georgia, and most of them (47 species) were described in the nature reserves of eastern, western and central Georgia. 46 species of earthworms (51,7% of Caucasian Lumbricidae) found in Georgia have been identified as endemic species of the Caucasus. The similarities of earthworms’ dominant species in the various ecosystems within the Algeti National Park are discussed in the paper. The high level of Caucasus fauna endemism is mainly caused by the unique natural and climatic conditions of the Caucasus, which is clearly expressed in the species composition of earthworms. Among the genera which compose the Caucasian Lumbricidae fauna, the genus Dendrobaena has the most species diversity with 22 species (24.71%), followed by Eisenia (9 species, or 10%). The six genera Bimastos, Eiseniella, Imetescolex, Lumbricus, Octodrilus, and Omodeoia are represented by a single species.